Capitalismo, Archive and Information - Rodríguez, Pablo Manolo (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
This text tries to summarize the main axes of the book Anarchivismo. Tecnologías políticas del archivo, by Andrés Maximiliano Tello. Within the so-called archival turn, the work focuses on a characterization of arcontic capitalism, which refers to a process of capitalist accumulation that has data and records, in their informational version, as its main asset. To this end, the contributions of some authors of poststructuralist French philosophy (M.Foucault, G.Deleuze and J.Derrida) are reviewed, then linked to the reflections of another central philosopher for the understanding of the challenges posed by the notion of information, such as J-F. Lyotard, and finally the tensions between the concepts of memory, imprint, inscription in different terrains are highlighted.